EDUKASI GIZI SEIMBANG MELALUI PERMAINAN ENGKLEK PADA REMAJA DI KOTA BANDUNG - Yakobus Lau De Yung Sinaga; Meda Yuliani; Sri Lestari Kartikawati; Fikri Mourly Wahyudi; Ahmad Mustopa (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
Diet is one of the things that is important for excellent health. Many studies have shown that there is a nutritional transition in Indonesia and this has affected the diet of adolescents. At this time adolescents consume more foods that are high in fat, salt and sugar. Therefore, this Community Service activity was carried out together with two partners, namely SMP Mekar Arum and SMP Bakti Nusantara 666 to increase knowledge about Balanced Nutrition. The method used in this community service activity is to conduct counseling and also education with a modified Engklek game. Through this activity, it was found that there was a significant increase in the knowledge of adolescents related to balanced nutrition after being given an intervention in the form of engklek games (p < 0.05). The educational activities ran smoothly and the participants seemed very enthusiastic about the game. In the future, it is hoped that more in-depth research will be conducted on the effect of cricket games on the practice of a balanced diet among adolescents in the city of Bandung